The reading and writing skills and their development into the teaching learning process with students of 1st, 2nd and 3rd years of high school curriculum at “Pio Jaramillo Alvarado” high school period 2009-2010 - ESCOBAR PEÑA, JOHANA MARICELA (2011)
The present research work entitled: the reading and writing skills and their development into the teaching learning process with students of 1st, 2nd and 3rd years of high school curriculum at “Pío Jaramillo Alvarado” high school period 2009-2010., has as a purpose to know the development of the reading and writing skills in the teaching learning process. We used different methods like descriptive, synthetic, analytic, and explicative, which helped us to prove if the outlined hypothesis were true or false and gave them a logical explanation. The instrument that helped us to get information was the survey; through it we obtained the necessary data to know which are the weakness and the straightness about the reading and writing skills. The main results that we found in the present research were that the techniques applied by teachers are not suitable to develop reading and writing skill and also the strategies and techniques applied by the teachers do not facilitate the development of the reading and writing skills in the teaching learning process with students of 1st, 2nd and 3rd years of high school curriculum at “Pío Jaramillo Alvarado” high school.